2012
DOI: 10.1002/jqs.2553
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen isotopes from Chinese caves: records not of monsoon rainfall but of circulation regime

Abstract: Oxygen isotope variations in Chinese stalagmites have been widely interpreted as a record of the amount of East Asian summer monsoonal rainfall. This interpretation infers decreasing monsoonal rainfall from the mid-Holocene and large, dipolar rainfall oscillations within glaciations. However, the speleothem d 18 O variations conflict with independent palaeoclimate proxies (cave d 13 C, loess/palaeosol magnetic properties, d 13 C alkanes), which indicate no systematic decline in rainfall from the mid-Holocene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
120
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(130 citation statements)
references
References 66 publications
(117 reference statements)
5
120
0
Order By: Relevance
“…However, recent studies have pointed out that the cave records in eastern Asia may have been misinterpreted so far, not portraying absolute precipitation but rather the source region of the moisture (e.g. Maher and Thompson, 2012). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies have pointed out that the cave records in eastern Asia may have been misinterpreted so far, not portraying absolute precipitation but rather the source region of the moisture (e.g. Maher and Thompson, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies pointed out that cave records in eastern China may not reflect absolute rainfall nor summer rainfall, but rather represent the moisture source (Maher, 2008;Cheng et al, 2012 and references therein; Maher and Thompson, 2012), and thus indicate the relative strength of the involved circulation systems (East Asian monsoon, Indian monsoon and Westerly wind system). A weakening of the Indian monsoon during the Holocene and the associated reduction in its inland penetration into eastern China may have strengthened the influence of the East Asian monsoon (oceanic source) trans- porting less depleted air from the Pacific to the caves (Maher and Thompson, 2012). Indeed, the transient simulations reveal an enhanced vertically integrated moisture flux from the Indian summer monsoon region into eastern China during the mid-Holocene (see Fig.…”
Section: Global Vs Regional Monsoon On Centennial To Millennial Timementioning
confidence: 99%
See 1 more Smart Citation
“…speleothems, some studies have suggested that the amount of precipitation could be mainly responsible for determining the water isotope concentration (Fleitmann et al, 2003;Wang et al, 2001) -this is called the amount effect (Dansgaard, 1964;Rozanski et al, 1992). Furthermore, in these regions δ 18 O and δD might also reflect convective activity along a moisture trajectory (Vimeux et al, 2005;Yao et al, 2012), changes to regional moisture sources, and the intensity or provenance of atmospheric transport pathways (LeGrande and Schmidt, 2009;Dayem et al, 2010;Lewis et al, 2010;Maher and Thompson, 2012;Caley et al, 2014a;Tan, 2014). High-resolution and well-dated records of δ 18 O of calcite in tropical speleothems in Asia or South America have therefore been interpreted in terms of past monsoon dynamics (Cruz et al, 2005;Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The stalagmite δ 18 O results from various sites indicate a uniform evolution history with the optimum cli-mate occurring in the early Holocene. However, stalagmite δ 18 O values are also influenced by seasonality of precipitation, moisture source and transport pathway, especially in eastern China (Breitenbach et al, 2010;Maher, 2008;Maher and Thompson, 2012;Pausata et al, 2011;Tan, 2014;Wang et al, 2001). In contrast, the timing and duration of the Holocene climatic optimum inferred from marine and lake sediment records differ from the speleothem record, possibly because of differences in temporal resolution, in the sensitivity of the proxy, and the lack of reliable chronologies (Hou et al, 2012;Sun et al, 2015;Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%